RAISE THE SPIRIT OF CONFIDENCE IN STUDENTS WHO HAVE MENTALLY WEAK DUE TO INTERNAL FAMILY PROBLEMS - Andika Bayanfkara; Siti Mayang Sari; Mhd Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Within the school environment, we encounter various problems faced by students and this becomes a challenge in itself for a teacher, when students have problems that may be faced at home or in the family environment, it really influences the learning process so that there is a decrease in the student's learning outcomes. There are many factors that can influence a student's enthusiasm and self-confidence, problems that arise in them, such as family, economics, parental support, and the incompleteness of one of the student's parents are very influential factors. This research uses a qualitative approach involving students who have experience of internal family problems. In-depth interview techniques were used to understand their perspectives and experiences in more detail. This approach of listening and providing active attention to students has proven effective in helping them feel heard and understood. The emotional support provided by teachers and school staff also has a positive influence in rebuilding students' self-confidence. Interventions involving counseling, social support from teachers, social skills development programs, and building self-identity, have been proven to have a positive impact in increasing students' self-confidence. This research provides valuable insight in raising the spirit of self-confidence in students who experience internal family problems. Strategies such as listening, providing emotional support, establishing positive relationships, engaging in extracurricular activities, and facilitating the development of clear goals can help students strengthen their self-confidence and overcome the negative impact of internal family problems.